(untitled) (Kinesiology, 2017)
The purpose of this study was to examine the effects of a one-session-per-week stretching program on hamstring extensibility among schoolchildren in the physical education (PE) setting. Thirty seven 9-year-old schoolchildren from two classes were clustered and randomly assigned to an experimental group (n=19) or a control group (n=18). During PE classes, the experimental students performed a 3-minute stretching program once a week throughout academic year (a total of 32 calendar weeks, but 28 weeks of intervention after excluding holidays). Hamstring extensibility (estimated by the classic sit-and-reach test) was assessed at the beginning (week 0), in the middle (week 18) and at the end (week 34) of the stretching intervention program. The results of the two-way analysis of variance showed that the PE-based stretching program improved statistically significantly the students’ sit-and-reach scores in the middle and at the end of the intervention (p<.01). Since in PE many curricular contents need to be developed each academic year and the subject is also restricted by its limited curriculum time allocation, teachers could improve students’ hamstring extensibility by only a one-session-per-week stretching program. Therefore, in addition to the improvement of students’ flexibility levels, this intervention program might permit regular development of other PE curricular contents. This knowledge could help and guide teachers to design programs that guarantee a feasible and effective development of flexibility in the PE setting. Key words: flexibility program, frequency, classic sit-and-reach test, health-related physical fitness, primary school, physical education setting